Effect of Metformin on some physiological parameters in patients of diabetes in Diwaniyah General Hospital - A. Alsudani, Arjwan (Al-Qadisiyah Journal of Pure Science, 2018)
The study aims to determine the effect of Metformin on some certain criteria in patients with type2 diabetes. Twenty five newly diagnosed type2 diabetic patients participated in this study. Ages ranged between 35-65years. Blood samples were taken from people infected before treatment and after three months of Metformin give them the drug dose (500 mg / day) twice a day and were compared with 25 people from a group of healthy control group. Then blood analysis for the purpose of measuring the level of cholesterol, triglycerides, lipoprotein high for density HDL, lipoprotein low for density LDL, liver enzymes (ALT, AST) and blood urea .The results showed a significant rise in the metformin group (before treatment) and the control group in cholesterol levels and triglycerides and lipoprotein low for density and a significant decrease in lipoprotein level of high density. The significant decrease in the level of cholesterol, triglycerides and lipoprotein low for density and high moral in high-density lipoprotein level range between Metformin group (after treatment) compared with Metformin group (before treatment) and the control group. Note also been a significant increase in liver enzyme levels compared between groups (after treatment) and (before treatment) and the control group.